Medicina e cirurgia no medievo : a circulação e o uso dos saberes médicos e seus aspectos de globalidade e conectividade a partir das obras de Henri de Mondeville e Guy de Chauliac (séc. XIII-XIV) - Damaceno, Mauricio Ribeiro (2024)
This study delves into the construction of medical knowledge during the Middle Ages, particularly in the 13th and 14th centuries, a period characterized by significant cultural changes and exchanges. The research highlights how medical knowledge was built through a complex process of transmission, assimilation, and renewal that transcended cultural, geographical, and temporal boundaries. The central figures and works in this process are La Chirurgie by Henri de Mondeville and Chirurgia Magna by Guy de Chauliac, court surgeons with privileged access to medical knowledge who actively contributed to the development of medieval medicine in their time. The research reveals a robust and resilient network of knowledge dissemination that overcame the geographical and religious barriers of the period. These networks not only connected distant individuals but also served as channels for the transmission of knowledge through manuscripts and oral tradition. The analysis of the manuscripts left by Henri de Mondeville and Guy de Chauliac underscores the importance of personal experiences in the construction of medical knowledge. Direct observation, practical experimentation, and the ability to adapt to challenging contexts were fundamental to the development of more effective theories and practices. This study seeks to understand how the combination of practical factors, global connections, sharing networks, and individual experiences influenced medicine in the Middle Ages. By exploring these multifaceted aspects, it aims to offer a new perspective on the construction of medical knowledge during the medieval period.